Scientific Mapping of English Language Teaching Research in the Philippines: A Bibliometric Review of Doctoral and Master's Theses (2010–2018). (April 2022) - Barrot, Jessie S.; Acomular, Denson R.; Alamodin, Editha A.; Argonza, Ria Cristina R.
Very few studies have comprehensively mapped out the landscape of English language teaching (ELT) research, particularly those that are not accessible to wider international readership. Thus, this bibliometric study examines ELT doctoral and master's theses in the Philippines. A total of 98 theses and dissertations completed between 2010 and 2018 were collected from various Philippine universities. Quantitative analysis was used to examine the characteristics and topical foci of the selected studies. Findings reveal that most of the theses and dissertations mainly focussed on only four ELT areas. The other 17 areas remain underexplored ( N = 11) or unexplored ( N = 6). Findings further suggest that there has been a lack of direction and slow expansion of ELT research areas in the country. This trend is primarily attributed to the absence of clear ELT research agenda. Implications for English language education, teacher education, and future direction for ELT research in the country are discussed.